Smart site monitoring system / Muhammad Azmi and Muhammad Naim Mahyuddin - Azmi, Muhammad; Mahyuddin, Muhammad Naim (2023)
The Smart Site Monitoring System is an innovative and integrated approach designed to optimise a construction site management. The primary objective of this project is to develop a comprehensive system that enhances real-time monitoring, improves safety protocols, and streamlines communication among stakeholders. The Smart Site Monitoring System utilises a network of Internet of Things (IoT) devices, including sensors and cameras, strategically installed across the construction site. These devices collect and transmit data to a centralised cloud-based platform. Advanced data analytics and machine learning algorithms process this data, enabling the system to detect potential safety hazards, monitor construction progress, and predict resource requirements. Throughout the project’s implementation, the Smart Site Monitoring System demonstrated remarkable efficiency gains, reducing project timelines by an average of 15% and preventing safety incidents by alerting supervisors in real-time. Additionally, the system;s predictive capabilities facilitated better resource allocation, leading to cost savings of up to 10%. This innovation holds significant implications for the construction industry, offering a proactive and data-driven approach to site management.